Preservice teacher mindshifts: artful stories and transformations. Issue 5 (3rd September 2021) - Arnold, Julie
ABSTRACT: This paper is an inquiry into preservice teacher learning insights by tracing transformative experiences of becoming a teacher. To do this, the article includes 4th year preservice teachers' stories in an attempt to highlight the positioning of transformative mindshift learning encounters. Here, preservice teachers describe learning from life experiences that underpin the path to teach. During the quest to become a teacher, preservice teachers often approach their future with confidence but at times with trepidation. Reflections derived from interviews capture and present some significant moments and strategic factors contributing to preservice teachers experiences and identity: (1) the nature of students' teaching and learning, content knowledge and approaches; (2) moral positioning and social commitment toward education and public good; (3) personal lifeworld experiences, (4) connections to family and habitus, and (5) notions of selfhood. Interviews are undertaken using an ethnographic and artful experimental method, foregrounding embedded reflection. Artful interplay assists the reflections to indicate the complexity of learning and elements of social, historical, political and cultural links traced as preservice teachers' journey through initial teacher education.